(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
In-situ leaching (ISL) has gained prominence as a non-destructive method for rare earth element (REE) extraction, particularly in regions like China. However, concerns over the environmental impact and soil stability due to ISL activities have surfaced following a landslide incident. This article distills the essence of a comprehensive research endeavor that delves into the effects of ammonium sulfate ISL leaching, employing concentrations of 0.05M, 0.1M, and 0.5M, on soil mechanical properties. The study encompasses physicochemical, physical, and mechanical tests, unveiling substantial alterations in shear strength, cohesion, angle of internal friction, zeta potential, liquid limit, plastic limit, and plasticity index following leaching. XRF and XRD analyses reveal the presence of REEs and distinctive mineral phases in the soil samples. Overall, ISL induces a weakening of the soil, raising concerns about potential slope failures and emphasizing the need for a deeper understanding of ISL’s impact on soil properties in the context of REE mining.